The role of catalysis for the sustainable production of bio-fuels and bio-chemicals - Triantafyllidis, Kostas S.; Lappas, Angelos A.; Stöcker, Michael (Elsevier, 2013)
Focuses primarily on the state-of-the-art catalysts and catalytic processes expected to play a decisive role in the "green" production of fuels and chemicals from biomass.